Socio‐economic Inequality in the Use of Procedures and Mortality Among AMI Patients: Quantifying the Effects Along Different Paths. (December 2015) - Hagen, Terje P.; Häkkinen, Unto; Iversen, Tor; Klitkou, Søren Toksvig; Moger, Tron Anders
Abstract: It is not known whether inequality in access to cardiac procedures translates into inequality in mortality. In this paper, we use a path analysis model to quantify both the direct effect of socio‐economic status on mortality and the indirect effect of socio‐economic status on mortality as mediated by the provision of cardiac procedures. The study links microdata from the Finnish and Norwegian national patient registers describing treatment episodes with data from prescription registers, causes‐of‐death registers and registers covering education and income. We show that socio‐economic variables affect access to percutaneous coronary intervention in both countries, but that these effects are only moderate and that the indirect effects of the socio‐economic factors on mortality through access to percutaneous coronary intervention are minor. The direct effects of income and education on mortality are significantly larger. We conclude that the socio‐economic gradient in the use of percutaneous coronary intervention adds to socio‐economic differences in mortality to little or no extent. Copyright © 2015 John Wiley & Sons, Ltd.